Avaliação do potencial biotecnológico do aspergillus spp. para produção de biomassa como recurso renovàvel na geração de energia - Leão, Nairane da Silva Rosa (2015)
In the last three decades, the search for alternative and renewable fuels had greater evidence on the world stage, due to growing environmental concerns and the prospect of depletion of fossil energy sources. The biomass of microorganisms has been suggested as suitable for conversion to energy. This study aimed to assess the biotechnological potential of Aspergillus spp. isolated from Caatinga through the selection of ten genre samples, Aspergillus niger (3), A. flavus (3), and A. parasiticus (4). Of total lipid extractions were performed and the sample with better percentage held the growth kinetics, characterization of fatty acids and antioxidant activity of selected sample. Samples were grown in synthetic medium Czapek liquid, and reciprocating means (molasses and corn steep liquor sugarcane), using the complete factorial design 23. The total lipids were extracted using binary combination of chloroform and methanol. Total lipid amounts were obtained over 20% in both culture media, featuring the genus Aspergillus as oleaginous. The results indicated that the Aspergillus parasiticus CPU 1132, an output obtained from 2.03 g / L of biomass production and a 44.2% total lipids in Medium Czapek while in alternative production medium (sugar cane molasses and corn steep liquor) obtained in the trial (8) 2,83g biomass to 48.9% of total lipids. The fatty acid profile grown in Czapek medium indicated the presence of acid g [[ raxos linoleic (36.54%) and oleic (33.95%). And alternative way to favor the production of the compound linolenic acid (28.66%) and linoleic acid (40%). In oxidant activity of Aspergillus parasiticus, calculated in linear regression, got the EC50 4.06774 mg / mL of lipid extract. This the results obtained from Aspergillus parasiticus CPU 1182, suggest important as a source of lipids for its use in biotechnological processes such as application and biofuels drugs.